Topological Optimization Design and Analysis of Ultra-short Harmonic Flexspline - Yan Li; Qiuping Liu; Yang Wang; Qianqian Liu (Jixie chuandong)
In order to study the ultra-short harmonic reducer with high performance， the topology optimization theory is introduced into the design of harmonic flexspline design. The objective function of stiffness is defined based on compromise programming method， and the topology optimization model of flexspline is constructed with constraints of volume fraction and processing technology. The optimization problem is solved by using the criterion of optimization algorithm based on Abaqus/ATOM software. The secondary design is carried out by using the SolidWorks， and through the finite element analysis， the rationality of results before and after optimization are verified. The method has practical significance for the design and optimization of ultra-short harmonic flexspline.